Medicare Current Beneficiary Survey, Calendar Year 1991: (United States) ([Verlag nicht ermittelbar], 1993)
This data collection is the first in a series of data releases planned from the ongoing Medicare Current Beneficiary Survey (MCBS). The MCBS is a continuous, multipurpose survey of a representative sample of the Medicare population. Sample persons are interviewed three times a year over several years to form a continuous profile of their health care experience. Field work for Round 1 began in September of 1991 and was completed in December. New rounds, which involve reinterviewing the same sample persons (or other appropriate respondents), begin every four months. Interviews are conducted regardless of whether the sample person resides at home or in a long-term care facility, using the questionnaire version appropriate to the setting. This first-round interview captured baseline information about the Medicare population, including their demographic characteristics (date of birth, sex, race, education, military service, and marital status), health status and functioning, insurance coverage, financial resources, and family support. Round 1 of the community interview, which questioned respondents living at home, also included a topical supplement on access to medical care, sources of medical care, and satisfaction with medical care.